IMPLEMENTATION OF THE GOGREEN MODEL IN OPTIMIZING ABILITY LITERACY WRITE NARRATION ELEMENTARY SCHOOL STUDENTS - Lukman Nugraha; Miptah Parid (El Midad, 2023)
This article aim for know implementation of learning models gogreen in optimizing ability literacy narrative participant educate school basic. Study This use method qualitative. Study This conducted in class 5 MIN 3 Subang. Deep data collection techniques study This use observation, interview and documentation. Findings study showing that participant students in class 5 MIN 3 Subang are optimal, namely seen from participant educate already carry out whole tapan gogreen model. The stages carried out in optimizing ability write narrative using the go-green model this that is as following : 1) grouping ie participant educate in shape become a number of group ; 2) organizing ie participant educate strategize together the group for see problem and search solution on topic narration to be made; 3) growing ie grow interest and love related topic created narrative with method look for reference; 4) reading ie read material from topic narrative to be made; 5) exploring ie participant educate explore knowledge and keywords topic narration to be made; 6) elaborating ie participant educate make product topic narrative then developed become essay narration ; and 7) narration that is participant educate tell a story through topic - oriented writing narration to be created. From the results study obtained that gogreen model can optimizing ability write narration. Basically a learning model gogreen this is a learning model for introduce to participant educate about love participant educate in write narration.